Analisis Data dalam Supply Chain Management: Klasifikasi dan Pemantauan Data Gudang PT Rajawali Nusantara Indonesia - Karen Natalie; Bakti Siregar (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
This internship report discusses the application of data analysis in supply chain management, with a focus on classification and monitoring of warehouse data at PT Rajawali Nusantara Indonesia. In this report, Excel and R Studio are adopted as data analysis tools to improve efficiency in warehouse management. This research covers two main aspects: first, implementation of a warehouse data classification system using R Studio and Excel to optimize the allocation and placement of goods. Second, using R Studio and Excel for real-time monitoring of warehouse activities, including item selection, delivery, and inventory conditions. Through an experimental approach and historical data analysis, this research evaluates the impact of using Excel and R Studio on operational efficiency and warehouse response speed. The results are expected to provide insight for companies in improving warehouse management.